Analysis of Quality of Work Life on Employee Job Performance Through Emotional Fatigue as a Mediating Variable - Handawani, Aprilia Salsiah; Ramdan, Asep Muhamad; Nurmala, Resa (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to determine the mediating effect of emotional exhaustion in the relationship between quality of work life and employee performance. The research method used in this research is quantitative research method with associative descriptive approach. The sample technique used was saturated sample by distributing questionnaires to 233 employees of Perumda Tirta Jaya Mandiri Sukabumi Regency and the data analysis technique was Structural Equation Modeling (SEM) with the help of AMOS software version 24. The results of this study indicate that Perumda Tirta Jaya Mandiri has succeeded in building quality of work life, emotional exhaustion, and good work performance in the eyes of employees. Quality of work life has a direct and significant effect on emotional exhaustion of 0.954, emotional exhaustion has a direct and significant effect on employee work performance of 0.965 emotional exhaustion mediates effectively in the relationship between quality of work life and employee work performance with an indirect effect of quality of work life on employee work performance of 0.982. The direct relationship effect of quality of work life on employee work performance is smaller than the indirect effect. Thus, it can be concluded that emotional exhaustion acts as a mediator of the relationship between quality of work life and employee work performance.